2015
DOI: 10.1080/10412905.2015.1023905
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antibacterial activitiy of the essential oils of AlgerianMyrtus communisL.

Abstract: Myrtus communis L. leaf essential oils from Algeria were analyzed by gas chromatography (GC) and gas chromatography/mass spectrometry (GC/MS). A total of thirty-four components were identified accounting for 95% of the oil. The main compounds were limonene (23.4%), linalool (15.4%), geranyl acetate (10.9%), α-pinene (10.7%), linalyl acetate (8.2%) and 1,8-cineole (6.6%).The antimicrobial evaluation showed that myrtle oil exhibited good antibacterial activity against Staphylococcus aureus, Proteus mirabilis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Finally, essential oil derived from myrtle plants has been shown to inhibit (a) the growth of different strains of Mycobacterium tuberculosis and Mycobacterium paratuberculosis , with MIC values ranging from 0.17 to ˃2% (Zanetti et al., 2010), (b) the growth of S. aureus , L. monocytogenes , E. coli , Enterococcus durans , Salmonella Thypi , P. aeruginosa , and B. subtilis , reporting MIC values between 0.5 and ˃1% ( P. aeruginosa ) (Akin, Aktumsek, & Nostro, 2010), (c) the growth of S. typhimurium deposited on shredded iceberg lettuce and on the skin of whole tomatoes (Gündüz, Gönül, & Karapinar, 2009), (d) the growth of S. aureus , P. mirabilis , and Klebsiella pneumonia , with MIC values ranging between 0.12 and 4 µg/ml (Hennia, Brada, Nemmiche, Fauconnier, & Lognay, 2015), (e) the growth of P. aeruginosa with MIC and MBC values of 64 µg/ml (Owlia, Saderi, Rasooli, & Sefidkon, 2009), (f) the growth of E. coli , S. aureus , and C. albicans , reporting MIC and MBC values of 2–4 and 4–8 µg/ml, respectively (Yadegarinia et al., 2006), and (g) the growth of a panel of 12 pathological microorganisms, including Gram‐positive and Gram‐negative bacteria, fungi, and yeast, as shown in Table 3 (Berka‐Zougali, Ferhat, Hassani, Chemat, & Allaf, 2012).…”
Section: Effects On Human Healthmentioning
confidence: 99%
“…Finally, essential oil derived from myrtle plants has been shown to inhibit (a) the growth of different strains of Mycobacterium tuberculosis and Mycobacterium paratuberculosis , with MIC values ranging from 0.17 to ˃2% (Zanetti et al., 2010), (b) the growth of S. aureus , L. monocytogenes , E. coli , Enterococcus durans , Salmonella Thypi , P. aeruginosa , and B. subtilis , reporting MIC values between 0.5 and ˃1% ( P. aeruginosa ) (Akin, Aktumsek, & Nostro, 2010), (c) the growth of S. typhimurium deposited on shredded iceberg lettuce and on the skin of whole tomatoes (Gündüz, Gönül, & Karapinar, 2009), (d) the growth of S. aureus , P. mirabilis , and Klebsiella pneumonia , with MIC values ranging between 0.12 and 4 µg/ml (Hennia, Brada, Nemmiche, Fauconnier, & Lognay, 2015), (e) the growth of P. aeruginosa with MIC and MBC values of 64 µg/ml (Owlia, Saderi, Rasooli, & Sefidkon, 2009), (f) the growth of E. coli , S. aureus , and C. albicans , reporting MIC and MBC values of 2–4 and 4–8 µg/ml, respectively (Yadegarinia et al., 2006), and (g) the growth of a panel of 12 pathological microorganisms, including Gram‐positive and Gram‐negative bacteria, fungi, and yeast, as shown in Table 3 (Berka‐Zougali, Ferhat, Hassani, Chemat, & Allaf, 2012).…”
Section: Effects On Human Healthmentioning
confidence: 99%
“…Low activity ( MIC values in the range of 4.5 – 18 mg/ml) was observed against six Gram ‐negative microorganisms . In parallel, myrtle leaf oil (composition dominated by limonene and linalool) has been reported to display antibacterial activity against Proteus mirabilis , S. aureus , and K. pneumoniae , while the essential oil was inactive against P. aeruginosa . However, the reported MIC values (0.12 – 4 μg/ml) were very low and differed drastically from all other values found in the literature .…”
Section: Biological Effects Of Algerian Myrtus Essential Oilmentioning
confidence: 78%
“…In two recent articles were reported oil samples from the forest of Bissa (Chlef) and from Ain Romana (Blida). The main compounds of the former (leaf oil) were limonene (23.4%), linalool (15.4%), geranyl acetate (10.9%), α ‐pinene (10.7%), linalyl acetate (8.2%), and 1,8‐cineole (6.6%) . The later (berry oil sample) contained predominantly the usual monoterpene hydrocarbons, limonene (12.9%), and α ‐pinene (10.0%), as well as octadienol (12.9%), a non‐terpene unsaturated alcohol not yet identified in myrtle oils .…”
Section: Chemical Composition Of Essential Oil From Algerian Myrtus Lmentioning
confidence: 99%
“…It has reported that essential oil of M. communis exhibits antibacterial effects against pathogenic bacteria, such as Staphylococcus aureus, Proteus mirabilis and Kleibsiella pneumonia (Hennia et al, 2015). Cannas et al (2014), found (Curini et al, 2003).…”
Section: In Vitro Antifungal Activitymentioning
confidence: 99%
“…There are various studies in the literature investigating the chemical composition of essential oils of M. communis (Zomorodian et al, 2013;Hennia et al, 2015). The essential oil of M. communis has been investigated efficiency of antimicrobial,…”
Section: Introductionmentioning
confidence: 99%